Carcinogenic potential of high aspect ratio carbon nanomaterials. Issue 3 (12th April 2016) - Luanpitpong, Sudjit; Wang, Liying; Davidson, Donna C.; Riedel, Heimo; Rojanasakul, Yon
Abstract : Review of recent advances in nanomaterial genotoxicity and carcinogenicity with a focus on lung carcinogenicity of high aspect ratio carbon nanotubes. Abstract : Engineered nanomaterials, including high aspect ratio carbon nanomaterials, are often commercialized without a complete human risk assessment and safety evaluation. A health concern has been raised that high aspect ratio nanomaterials such as carbon nanotubes may cause unintended health consequences, such as asbestos-like lung cancer and mesothelioma, when chronically inhaled. Considering the widespread industrial and clinical applications and the increasing incidence of human exposure to nanomaterials, it is important to address the issue of nanomaterial carcinogenicity in a timely manner. This review summarizes recent advances in nanomaterial genotoxicity and carcinogenicity with a focus on high aspect ratio carbon nanotubes, and discusses current knowledge gaps and future research directions.